Antileishmanial activity of Clinanthus milagroanthus S. Leiva & Meerow (Amaryllidaceae) collected in Peru (2023)
Leishmaniasis is a worldwide infectious parasitic disease caused by different species of protozoa of the genus Leishmania, which are transmitted to animals and humans through the bite of insects of the Psychodidae family. In the present work, the antileishmanial activity of an alkaloid extract of the bulbs of Clinanthus milagroanthus S. Leiva & Meerow (Amaryllidaceae) was evaluated in vitro, in vivo, and in silico against the parasite Leishmania braziliensis, and the chemical profile of the sample was determined by GC-MS analysis. At concentrations of 1, 10, and 100 µg·mL−1, the alkaloid extract presented inhibition percentages of 8.7%, 23.1%, and 98.8%, respectively, against L. braziliensis with a p < 0.05, and IC50 values of 18.5 ± 0.3 µg·mL−1. Furthermore, at a dose of 1.0 mg·kg−1, a greater decrease in lesion size was observed (90%) for in vivo assays, as well as a decrease in infection (96%), finding no significant differences (p > 0.05) in comparison with amphotericin B (92% and 98%, respectively). Eleven alkaloids were identified in C. milagroanthus bulbs: galanthamine, vittatine/crinine, 8-O-demethylmaritidine, anhydrolycorine, 11,12-dehydroanhydrolycorine, hippamine, lycorine, 2-hydroxyanhydrolycorine, 7-hydroxyclivonine, 2α-hydroxyhomolycorine, and 7-hydroxyclivonine isomer. A molecular model of Leishmania braziliensis trypanothione reductase (TRLb) was built using computational experiments to evaluate in silico the potential of the Amaryllidaceae alkaloid identified in C. milagroanthus toward this enzyme. The structures galanthamine, 7-hydroxyclivonine isomer, and crinine showed better estimated free energy of binding than the reference compound, amphotericin B. In conclusion, this is the first in vitro, in vivo, and in silico report about the antileishmanial potential and alkaloid profiling of the extract of C. milagroanthus bulbs, which could become an interesting source of bioactive molecules